Digital Co-production in Archaeology. An editorial - Chiara Bonacchi; Bodil Petersson (Internet Archaeology, 2017)
This special issue focuses on digitally-enabled co-production in archaeology, by bringing together papers that were presented at the session Communication as Collaboration: Digital Methods, Experiences and Values, organised at the 21st Annual Meeting of the European Association of Archaeologists (University of Glasgow, 2015). The session was part of the Communicating Archaeology thematic cluster, which was partly inspired by the first published volume dedicated specifically to the topic of digital public engagement in archaeology (Bonacchi 2012). In that session and in this collection, we have been exploring communication as the collaborative construction of materials and interpretations rather than the dissemination of content at given stages of the archaeological research process (Bonacchi and Moshenska 2015).